Analysis of caesarean section rates using Robsons ten group classification: the first step - Koteshwara, Sowmya; M. S., Sujatha (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2017)
Background: The Caesarean section (CS) rate is steadily increasing worldwide including India. The overall CS rates are reported but rarely the women are classified. According to WHO Robson ten –group classification is useful as a global standard for assessing, monitoring and comparing cesarean section rates. Our objective was to classify women delivering in our hospital according to various categories as per the 10-group classification (Robsons classification) and analyzing the CS rate in each group. Methods: This was a cross sectional study conducted at JSS Medical College, Mysore. The data was collected for all women delivering in hospital from January 2016-December 2016 and the women were classified according to Robsons 10 group classification. The proportion of women delivering in each group, the CS rate of each group, and the relative contribution to CS rate from each group was calculated. Results: Among a total of 5016 women delivering during the study period 37.65% of women were delivered by CS. Maximum no of pregnant women belonged to primigravida group (group 1 and 2). Major contributor to CS rate were primigravida (group 2) at 32.2%. Next contributors were group 5 and group 1 at 28.9 % and 18.6% respectively. Overall the three groups 1, 2 and group 5 contributed to 79.7% of the CS rate while the other group contributed to only 21.3% of CS rate. Conclusions: Applying Robsons criteria to classify pregnant women allowed for easy classification to identify the category of women most likely to have CS. Reducing primary CS rate and increasing VBAC rates will help to reduce CS rate.